Structure-Activity Correlations for β-Phenethylamines at Human Trace Amine Receptor 1 - Lewin, Anita H. (2008)
A cell line in which RD-HGA16 cells were stably transfected with the hTAAR 1 receptor was created and utilized to carry out a systematic evaluation of a series of β-phenethylamines. Fair agreement was observed with data obtained for aryl and ethylene chain substituted analogs in an AV12-664 cell line in which hemagglutinin-tagged hTAAR 1 was stably co-expressed with rat Gα(s). Analogs with multiple substituents as well as analogs with bulky groups were found to be partial agonists. Analogs in which the primary amino group was converted to a secondary or a tertiary amino group by N-methylation were also partial agonists. Comparative Molecular Field Analysis (CoMFA) using the potency data yielded a regression coefficient r2 of 0.824. The steric field contribution to the model was 61% with the balance (39%) contributed by the electrostatic field. The collective results suggest that increasing steric bulk at both the amino nitrogen, particularly by N-dimethylation, and at the 4-position of the aromatic ring, leads to low efficacy ligands.